Program kemitraan masyarakat stimulus (pkms) gizi masyarakat pesisir : Program kemitraan masyarakat stimulus (pkms) gizi masyarakat pesisir - Riska Yanuarti; Henni Febriawati; Wulan Angraini; Tenia Desenze; Vica Sekarsari; Irfana Syafitri; Ahmad Syarizal Sidiq; Exsa Akhirullah; Rahmad Lendo; Parwito Parwito (Gayaku Publisher, 2025)
Increasing knowledge and providing information to the community in Lempuing Village, Bengkulu City, RT 11 RW 03, about coastal community nutrition. The objectives are to increase knowledge about the importance of nutrition, present material related to coastal community nutrition, play the Tricky Card Game, ensure that the community understands the information provided by the extension team, and reduce the prevalence of malnutrition in coastal communities. The method used was education related to nutrition in coastal communities. Obstacles to this coastal community nutrition education activity were that not many residents were able to participate in this activity because many residents went to work and had other commitments that could not be abandoned. In addition, there were some residents who did not show an increase in knowledge. This may be because each person has a different rate of information absorption and each person has a different level of attention. A strategic step to assess the success of the outreach program is for the team to visit the Lempuing Village community to coordinate further with the community. If the outreach program is successful, the next steps will be discussed.